ANALYSIS EFFICIENCY OF LUWAK COFFEE BUSINESS - Niken Dwinora; Eko Sumartono; Bambang Sumantri (AGRITROPICA : Journal of Agricultural Sciences, 2018)
The purposes of this study were to 1) Calculate the amount of profit from the civet coffee processing business in Bandung Jaya Village, Kabawetan District, Kepahiang Regency. 2) To calculate the efficiency of the civet coffee business in Bandung Jaya Village, Kabawetan Subdistrict, Kepahiang Regency, with consideration that in Bandung jaya Village, Kabawetan Subdistrict, Kepahiang Regency has the most sought after sales of civet coffee. Sampling was done by using the Purposive Method. Because the researchers intentionally took the data in the Luwak Coffee business stamp well in Bandung Jaya Village, Kabawetan District, Kepahiang District, the data analysis used the R / C ratio and B / C methods. The results showed that the efficiency analysis of R / C Ratio showed that Luwak coffee business was very efficient because revenues were greater than the total production costs. The results of the B / C Ratio analysis showed that these business ws not feasible because income is lower than the total production cost.